COVID-19 and virtual classroom: the effect on motivation of UiTM Puncak Perdana students / Siti Nur Aidah Johari and Mohd Shamsul Mohd Shoid - Johari, Siti Nur Aidah; Mohd Shoid, Mohd Shamsul (Faculty of Information Management, 2022)
The COVID-19 pandemic has spread around the world and has had a major impact on all universities, especially UiTM Puncak Perdana. This study would like to determine the students' motivation about virtual classrooms, which focuses on postgraduate students at the Faculty of Information Management, UiTM Puncak Perdana. This research is aimed to determine whether use of virtual classrooms application at postgraduate UITM Puncak Perdana level leads to affect students' motivation in the field of learning. This paper proposes a framework to determine three categories concerning the perspective on student motivation using virtual classrooms. As a result, the study reveals that the perspective on student motivation using virtual classrooms consists of learning design perspective, learner trait perspective and situational perspective. This paper also shows the table analysis of review and the figure proposed in the research framework. The quantitative approach and questionnaire instrument are the research methodology and technique used to investigate this phenomenon. Thus, this study is hoped to give a crystal clear understanding of the COVID-19 and virtual classroom affect the student motivation by postgraduate student of UiTM Puncak Perdana.